Bakteri Indigen yang Diisolasi dari Danau Toba: Acinetobacter junii DT2.1 Multiresisten Tembaga, Methylen Blue, dan Basic Fuchine - Irawati, Wahyu; Ambarita, Polin P.; Shaday, Vannesa El; Rahmawati, Sintia Y. (Jurnal Biologi Papua, 2023)
Lake Toba is one of the industrial waste disposal sites around the location. Copper and dyes are pollutants that are toxic and harmful to organisms. Bioremediation using indigenous bacteria isolated from polluted sites is a promising solution to overcome environmental pollution. Bacteria that have multi-resistance to copper and dyes are expected to increase the efficiency of industrial waste treatment. This study aims to: 1) isolate and characterize copper-resistant bacteria, 2) determine the level of resistance of bacterial isolates to copper, 3) test the resistance of bacteria to dyes. Physiological characterization of bacterial isolates was carried out by observing colony and cell morphology, also Gram staining. Molecular characterization was carried out by analysis of the 16S rDNA gene. The copper resistance level was tested by determining the Minimum Inhibitory Concentration MIC value. The dye resistance test was carried out by growing bacteria on a medium containing 100 ppm of dye. There were eight isolates of copper-resistant bacteria with MIC values ranging from 3-7 mM CuSO4 with code as DT1.1; DT1.2; DT1.3; DT1.4; DT1.5; DT2.1; DT2.2; and DT3.1. The three highly resistant bacteria were strains DT1.1 and DT1.3 which were identified as Lysinibacillus macroides and strain DT2.1 was identified as Acinetobacter junii with an MIC value of 7mM CuSO4, respectively. The results of the resistance test to dyes showed that only A. junii strain DT2.1 was resistant to 100 ppm Methylene Blue and Basic Fuschine.  Key words: indigenous bacteria; Lake Toba; multi-resistence; dye; copper.